A study on the lactation and reproductive performances of purebred Jersey stock: implications for introducing European dairy breeds in the tropical environment - Didanna, H. L.; Asmirew, L. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
To fulfil market demand, high-yielding temperate dairying breeds have been introduced to the tropics to boost dairy production. The tropical environment may impact the expression of the genetic potential of improved European breeds. Jersey breed has certain valued traits, i.e., small body size, low maintenance requirement, and milk quality. However, there is lack of empirical evidence on the perfor-mance of the Jersey breed, despite their huge dairy potential and contribution in East Africa. This study was carried out to investigate milk production and reproductive performance of Jersey dairy stock and related environment factors at Wolaita Sodo dairy breeding center. Data from 1164 records from 2008 to 2023 of purebred Jerseys were used and summarized by descriptive statistics, and General Linear Models of SPSS to analyze the effects of different factors on the performance parameters. The results revealed that the overall means for lactation milk yield (LMY), milk yield (DMY), and lactation length (LL) were 1852.5±21.5 litres, 5.5±0.07 litres and 337.2±2.5 days, respectively. LMY, LL and DMY were influenced by calving year and parity. There was a significant interaction among year, season of calving, and parity on LMY. Environmental influence (milking season, and period), and stage of lacta-tion were significantly affected milk yield. The overall means of age at first service (AFS), age at first calving (AFC), calving interval (CI), days open (DO), and number of services per conception (NSPC) were 23.2±0.4 months, 34.9±0.5 months, 462.7±8.1 days, 186.9±7.0 days, and 1.89±0.05, respectively. All reproductive performance traits were significantly influenced by the year of birth/service. CI and DO were influenced by the calving season and parity. Management inconsistency and climate fluctua-tion appear to have a significant impact on cow productivity and reproductive efficiency. Performance levels such as AFC and NSPC are comparable with other results for Jersey herds in tropical countries but far below the genetic ability of the breed, particularly in terms of LMY. Therefore, improvements in management practices, feeding levels, and health management would be critical. Moreover, the study implied that farm-bred/adapted pure European or crossbred dairy cows are appropriate for the high-lands and mid-altitudes in the tropical climate.